Ricotta cream: classification based on moisture and fat content considering general standards for cheeses and cream cheeses - Mykaell Yan Muniz de Souza (Elsevier, 2021)
Ricotta cream though an emerging product sold in Brazil, by 2021 it has no fixed quality standards, a condition that can result in products with variable composition and properties. Additionally, there are no methods of sampling or analysis for its official control. In this context, this study investigated the physicochemical quality of five Brazilian ricotta cream brands to verify the extent of differences in the composition of this product, emphasizing the characterization and classification according to the Brazilian legislation and the Codex Alimentarius standards. Significant differences between brands concerning pH, titratable acidity, moisture, ash, fat, and fat in dry matter (FDM) were observed (P < 0.05), which were probably a result of their heterogeneous ingredient composition. According to Brazilian regulatory standards, all samples fit the “very high moisture” definition, and the brands A, B, D and E achieved the classification of “high-fat cheeses” since they contained at least 60.0% of FDM. Brand C was the only product that could be classified as a “medium fat cheese” due to having FDM values between 25.0% and 44.9%. All samples fit the Brazilian and Codex Alimentarius classification for “cream cheeses” based on their moisture, dry matter content, moisture on a fat-free basis and FDM. The results reinforce the need for regulatory standards regarding the physicochemical quality and composition of this cheese variety, to guarantee more transparency for the consumers and that they have access to more homogeneous products.